Silver nanoparticles can be sampled by ultrafiltration probe but elution into & recovery from plasma and Dulbecco’s Phosphate Buffered Saline differs in vitro - Risselada, Marije; McCain, Robyn R.; Bates, Miriam G.; Anderson, Makensie L. (PeerJ, 2024)
Locally sustained release antimicrobials such as silver nanoparticles (AgNPs) might prove useful in combating local infections. Their elution has been investigated in Phosphate Buffered Saline (PBS) including from poloxamer 407 (P407). No information exists on possible interactions with proteins, nor have ultrafiltration (UF) probes been evaluated to measure Ag. These investigations would provide helpful data prior to investigating the sustained release after subcutaneous implantation in vivo over time. We compared (1) the influence of elution fluid on AgNP elution, and (2) UF probe and direct sampling in vitro. Six AgNP-P407 specimens in a dialysis tube were placed in Dulbecco’s PPBS (DPBS) (n = 3) or canine plasma (n = 3) for 96 h on a stirred hot plate (37 °C and 600 rpm) and sampled 20 times. A 0.001 mg/mL AgNP solution was prepared in DPBS or plasma. Six pipette and UF probe samples were taken of each. Inductively coupled plasma mass spectrometry was used to analyze Ag. Stock plasma contained Ag. At 96 h, 5/6 dialysis tubes had not fully released AgNP. One peak in hourly Ag increase was present in DPBS (10–13 h), and two peaks in plasma (6–8 and 10–13 h). The hourly Ag increase in plasma decreased earlier than in DPBS. Ultrafiltration probe sampling was possible in both DPBS and plasma and resulted in higher Ag concentrations but with more variation. While in vitro use of DPBS might be more cost effective, plasma should be considered due to difference in elution and recovery. Ultrafiltration probes can be used to sample Ag, but results will have a greater degree of variation, and multiple samples and increased time points should be considered.
Keywords: Elution; Ultrafiltration probe; in vitro; Silver nanoparticles’; Plasma; Canine